국내산 주요 침엽수 잎의 추출성분 (2) - 화백나무 (Chamaecyparis pisifera (Sieb. et Zucc.) Endlicher)잎 추출성분 및 항산화 활성 - 이상극; Sang Keug Lee; 배영수; Young Soo Bae (목재공학, 2006)
The dried ground needles (2.0 kg) of Chamaecyparis pisifera (Sieb. et Zucc.) Endlicher were extracted with acetone-$H_2O$ (7:3, v/v), concentrated, and fractionated with a series of n-hexane, methylene chloride, ethyl acetate and water on a separation funnel. Each fraction was freeze dried, then a portion of ethyl acetate soluble powder was chromatographed on a Sephadex LH-20 column using a series of aqueous methanol and ethanol-n-hexane mixture as eluents. The isolated compounds were identified by cellulose TLC, $^1H$-, $^{13}C$-NMR, COSY, HETCOR, FAB and EI-MS. (+)-catechin, taxifolin-3-O-${β}$-D-xylopyrano-side, quercetin-3-O-${α}$-L-rhamnopyranoside were isolated from the ethyl acetate soluble fraction of Chamaecypairs pisifera needle. Antioxidative tests on the isolated compounds indicated that all of the compounds showed similar values to ${α}$-tocopherol and BHT as controls. 화백나무(Chamaecyparis pisifera (Sieb. et Zucc.) Endlicher) 잎을 채취하여 건조시킨 후 분쇄하여 2.0 kg을 acetone-$H_2O$ (7:3, v/v)로 추출하고 헥산, 메틸렌클로라이드, 에틸아세테이트 및 수용성으로 분획하여 동결건조시켰다. 에틸아세테이트용성 분획을 sephadex LH-20으로 충진한 칼럼에서 메탄올과 에탄올-헥산 혼합액을 용리용매로 사용하여 칼럼크로마토그래피를 실시하였다. 단리된 화합물들은 TLC로 확인한 후 $^1H$-, $^{13}C$-NMR, COSY, HETCOR 등의 스펙트럼을 사용하여 정확한 구조를 규명하였고 FAB-MS로써 분자량을 측정하였다. 화백나무 잎의 에틸아세테이트 가용부에는 (+)-catechin (화합물 I), taxifolin-3-O-${β}$-D-xylopyranoside (화합물 II), quercetin-3-O-${α}$-L-rhamnopyranoside (화합물 III)가 분리되었으며 단리 화합물에 대한 항산화 실험에서는 화합물 모두 기준물질과 유사한 높은 항산화 활성을 나타내었다.